The Potential of Teak Forest Local Wisdom as a Learning Resource in Science, Technology, Engineering, and Mathematics Education: A Bibliometric Analysis of Problem-Solving Skills - Chozy Eka Nur Yahya; Endang Susantini; Lisa Lisdiana; Muhammad Zahrudin Afnan; Corrienna Abdul Talib (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
The integration of science, technology, engineering, and mathematics (STEM) learning with local wisdom has received increasing attention. However, its potential for utilizing local wisdom as an authentic learning context still requires further investigation. This study aims to map research trends in local wisdom-based STEM learning, examine research themes and their relationship with sustainable development goals (SDGs) 4 and 15, and analyze the potential of teak forest local wisdom in STEM learning to enhance students’ problem-solving. This study employed a bibliometric approach combined with a systematic literature review (SLR). Data were obtained from Scopus indexed articles published between 2006-2026 through the stages of data retreival, screening, data cleaning, analysis, visualization, and interpretation. Bibliometric analysis was conducted using microsoft excel, VOSviewer, and biblioshiny. The results indicate that publications on local wisdom-based STEM learning have increased, particularly during the 2024-2025 period, and are dominated by themes related to science education, STEM, local wisdom, and environmental issues. The emerging themes demonstrate a relationship between SDGs 4 and 15. However, the use of terrestrial ecosystems as a context for STEM learning and problem-solving skills (PSS) has not yet become a major focus. The synthesis results show that the local wisdom employed is contextual, closely related to students’ environments, and incorporates real world problems. Therefore, teak forest local wisdom has the potential to serve as an authentic context in STEM learning to support PSS while simultaneously connecting SDGs 4 and 15